2021
DOI: 10.1109/access.2021.3067696
|View full text |Cite
|
Sign up to set email alerts
|

Joint Decision-Making Model for Production Planning and Maintenance of Fully Mechanized Mining Equipment

Abstract: With the development of complex and intelligent sizeable mechanical equipment, the conflict between maintenance and production is becoming increasingly severe, restricting coal mine enterprises' production and development. This paper proposes a joint decision-making model for production planning and maintenance of fully mechanized mining equipment to solve the conflict between production and maintenance. Taking fully mechanized mining equipment as the research object and minimizing the total cost as the joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Based on this strategy, comparison of these models is tabulated in table 1 Based on this evaluation, it can be observed that Ens. [2], RL DTW [8], TDM [17], 3WD MA DM [20], TOP SIS GRA [28], IT2F DP [35], RNN Bi LSTM [36], RAD DRL [38], HG WOA [43], DPF CDT [46], and DM GAN [49] showcase higher contextual accuracy, which makes them highly useful for accurate decision recommendation use cases. It can also be observed that TF ADM [5], HG WOA [43], and DPF CDT [46] showcase lower computational complexity, thereby making them useful for low complexity decision recommendation scenarios.…”
Section: Results Analysis and Comparisonmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on this strategy, comparison of these models is tabulated in table 1 Based on this evaluation, it can be observed that Ens. [2], RL DTW [8], TDM [17], 3WD MA DM [20], TOP SIS GRA [28], IT2F DP [35], RNN Bi LSTM [36], RAD DRL [38], HG WOA [43], DPF CDT [46], and DM GAN [49] showcase higher contextual accuracy, which makes them highly useful for accurate decision recommendation use cases. It can also be observed that TF ADM [5], HG WOA [43], and DPF CDT [46] showcase lower computational complexity, thereby making them useful for low complexity decision recommendation scenarios.…”
Section: Results Analysis and Comparisonmentioning
confidence: 99%
“…In terms of computational delay or response time, TF ADM [5], RL DTW [8], TOP SIS GRA [28], IT2F DP [35], HG WOA [43], CRP [48], and DM GAN [49] are observed to have faster response, thus can be deployed for real-time use cases. While, LTBP STDP [12], TOP SIS GRA [28], IT2F DP [35], RNN Bi LSTM [36], RAD DRL [38], DEMA TEL [47], and DM GAN [49] showcase high recommendation efficiency, which makes them suitable for critical decision recommendation scenarios.…”
Section: Results Analysis and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Adam et al (2020) proposed the binary WOA (bWOA) to solve user-base station (BS) association and sub-channel assignment problems. Cao et al (2021) proposed a hybrid genetic WOA (HGWOA) that optimizes purchased equipmentโ€™s production planning and maintenance processes. El-Kenawy et al (2020) proposed a stochastic fractal search (SFS)-based guided WOA (SFS-Guided WOA) and performed feature classification balancing experiments on it based on COVID-19 images to achieve high accuracy classification prediction of COVID-19 diseases.…”
Section: Introductionmentioning
confidence: 99%